Transformation of CO2 to C2+ alcohols by tailoring the oxygen bonding via Fe-based tandem catalyst - Wenhang Wang; Xiangyu Guo; Yang Wang; Simin Lin; Xinhua Gao; Jie Liang; Jinqiang Zhang; Jinghao Xie; Hu Jiang; Fengliang Cao; Yongjie Chen; Guohui Yang; et al. (Nature Communications)
Abstract Direct conversion of CO2 into valuable organic products is probably the most important but challenging issue for global sustainability efforts. Metal carbides are promising as vital catalytic components in achieving this goal. Understanding the evolution of chemical orbitals and the corresponding energy levels on their interfaces are essential for targeted product synthesis. In this study, we discover that a highly active FeCo alloy carbide has a distinctive oxygen-bonding ability to regulate the evolution of oxygen-containing reaction intermediates. Combining with the copper/zinc/aluminum catalytic component, the designed tandem catalyst allows for the extremely high C2+ alcohols selectivity (49.1 percent) and space-time yield (245.7 milligram per gram catalyst per hour) at a CO2 conversion of 51.1 percent. The excellent catalyst stability (>1000 hours) and potential economic viability make this process promising in eliminating carbon emissions at industrial application scale.